Research on the Influence Path of Online Consumers’ Purchase Decision Based on Commitment and Trust Theory - You, Yan; Hu, Yanchuan; Yang, Weining; Cao, Shuai (Frontiers in Psychology, 2022)
Based on the theory of commitment and trust, this paper constructs an online consumer purchase decision model, empirically studies the common values, online trust, commitment and purchase decision, and explores the influence mechanism and path of online consumer purchase decision. The results show that common values of shopping platforms and online consumers have a significant positive impact on trust and commitment, among which the common value orientation of mutual trust and commitment compliance has the most significant impact, which reflects the core content of common values. Secondly, the confidentiality of buyer information, common value of ethics, accurate disclosure of information, and finally the attitude to solve problem;The establishment of online trust has a significant positive impact on commitment, and both online trust and commitment are positively related to purchase decision. In terms of research methods, the theory of commitment and trust is introduced into the study of online consumption on Chinese shopping platforms, which expands the scope of application of the theory of commitment and trust. The trust of online consumers is generated by their own shopping experience.The conclusion of this study provides a decision-making basis for the innovation of marketing model and has theoretical reference value.